Penerapan Massage Effleurage dengan Olive Oil terhadap Pencegahan Luka Dekubitus di Wilayah Kerja Puskesmas Sukoharjo - Nisa Eka Mufidah; Sri Hartutik (NAJ Nursing Applied Journal, 2024)
Background: The incidence of decubitus wounds in Indonesia was 33.3%, which is still high compared to Southeast Asia. Data from Central Java Hospital showed decubitus wounds reaching 30%, and the incidence in Sukoharjo City was 0.5%–1% in each region. Pressure on the skin caused by prolonged bed rest or immobilization can change the shape of the soft tissue in the bone protrusion area and increase the risk of decubitus. Objective: To describe the effects of implementing Massage Effleurage with Olive Oil on the prevention of decubitus wounds in bedrest patients. Methods: This kind of study employs descriptive research techniques, such as case studies, observation of two bedridden respondents, and application of olive oil massage therapy twice daily for five days, as assessed by the Braden Scale. Results: The category of decubitus score before application is moderate score and mild score. The category of decubitus score after application is mild score and mild score. There is an increase in decubitus score after being given effleurage massage with olive oil on both respondents. Conclusion: there is a change after giving effleurage massage with olive oil to decubitus scores in bedrest patients.